New iterative algorithms with self-adaptive step size for solving split equality fixed point problem and its applications. (2nd January 2023) - Tang, Yan; Zhou, Haiyun
Abstract : The purpose of this paper is to propose a new alternative step size algorithm without using projections and without prior knowledge of operator norms to the split equality fixed point problem for a class of quasi-pseudo-contractive mappings. Under appropriate conditions, weak and strong convergence theorems for the presented algorithms are obtained, respectively. Furthermore, the algorithm proposed in this paper is also applied to approximate the solution of the split equality equilibrium and split equality inclusion problems.